PENGARUH MEDIA BUSY BOOK TERHADAP KEMAMPUAN BAHASA RESEPTIF ANAK USIA DINI USIA 4-5 TAHUN DI KB KASIH IBU BEKASI - Alam, Kania Nur; Darmiyanti, Astuti; Riana, Nancy (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
Early childhood education (ECED) in Indonesia is regulated by Law No. 20/2003. This law emphasizes the importance of the education stage for children aged birth to six years. The purpose of this study was to find out how the use of Busy Book media impacts the receptive language skills of four- to five- year-old children at KB Kasih Ibu. Sixteen children from group A were given a pretest-posttest design to measure changes in their language ability after eight learning sessions using Busy Book. The pretest results, with a total score of 593 and an average of 60.43, showed that the receptive language skills of the children in group A had improved. In the hypothesis test using paired samples T-test, the tcount value (19.554) was greater than the ttable value (1.746), and the significance value (0.001) was smaller than 0.05. The results show that Busy Book books have a significant positive effect on the receptive language skills of children aged 4-5 years at KB Kasih Ibu Bekasi. This study concludes that Busy Book books are effective in improving children's receptive language skills at the PAUD stage.